Numerical Simulation of Temperature Field in Steel under Action of Electron Beam Heating Source; Key Engineering Materials; Vol. 712 : Advanced Materials for Technical and Medical Purpose (AMTMP 2016) - Skeeba V. Y. Vadim; Ivancivsky V. V. Vladimir; Martyushev N. V. Nikita Vladimirovich; Lobanov D. V. Dmitry; Vakhrushev N. V. Nikita; Zhigulev A. K. Aleksey (Electrophysical and Electrochemical Methods and Technologies of Materials Treatment, 2016)
Title screen